ANALYSIS OF DEVICES USED IN AERODYNAMIC TESTING (Journal of Multidisciplinary Sciences and Innovations, 2025)
Aerodynamic testing plays a critical role in modern automotive engineering, enabling accurate analysis of vehicle airflow behavior and drag coefficients. To simulate real-world conditions and validate computational models, specialized devices are employed in wind tunnels and laboratory environments. This study examines the key components involved in aerodynamic testing, including scaled car models, wind tunnels, smoke generators, force measurement systems, and digital sensors. The objective is to analyze the efficiency, accuracy, and integration of these devices in experimental procedures. Through this analysis, the study provides insights into optimizing testing methodologies to achieve better precision in aerodynamic design and development.